PENGARUH PERSEPSI TERHADAP KESIAPAN KERJA MELALUI KEPUASAN PRAKTEK KERJA LAPANGAN MAHASISWA PERGURUAN TINGGI VOKASI PARIWISATA - Priyanto Priyanto; Setyo Widiarto; Roby Darmadi; Nurti Rahayu (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2023)
On the Job Training (OJT) as part of the tourism vocational education curriculum is more than just a requirement to meet the adequacy of student graduation credits, OJT is required to provide student experience and competence to work after graduation. This study aims to determine work readiness which is determined by the perception and satisfaction of student OJT . This is a quantitative research utilizing the Structural Equation Model (SEM) as an analysis method. Utilizing the Work Readiness Scale (WRS) to quantify the level of student work readiness, the research results revealed that student perceptions did not significantly affect student OJT satisfaction, student OJT perception and satisfaction had a positive and significant effect on work readiness, while an indirect relationship between student perceptions of work readiness through OJT satisfaction showed insignificant results. These results conclude that factors that affect job satisfaction during the implementation of OJT have a significant impact on student work readiness. In the end, tourism vocational universities are required to be able to manage OJT well as an effort to create graduates who have competence and are ready to work and are highly competitive in the business world.